A novel tribological study on DLC-coated micro-dimpled orthopedics implant interface - Choudhury, Dipankar; Urban, Filip; Vrbka, Martin; Hartl, Martin; Krupka, Ivan (Journal of the mechanical behavior of biomedical materials, 2015)
This study investigates a tribological performance of diamond like carbon (DLC) coated micro dimpled prosthesis heads against ceramic cups in a novel pendulum hip joint simulator. The simulator enables determining friction coefficient and viscous effects of a concave shaped specimen interface (conformal contact). Two types of DLC such as hydrogenated amorphous carbon (a-C:H) and tetrahedral amorphous carbon (Ta-C) and one set of micro dimple (diameter of 300µm, depth of 70µm, and pitch of 900µm) were fabricated on metallic prosthesis heads. The experiment results reveal a significant friction coefficient reduction to the 'dimpled a-C:H/ceramic' prosthesis compared to a 'Metal (CoCr)/ceramic' prosthesis because of their improved material and surface properties and viscous effect. The post-experiment surface analysis displays that the dimpled a-C:H yielded a minor change in the surface roughness, and generated a larger sizes of wear debris (40-200nm sized, equivalent diameter), a size which could be certainly stored in the dimple, thus likely to reducing their possible third body abrasive wear rate. Thus, dimpled a:C-H can be used as a 'metal on ceramic hip joint interface', whereas the simulator can be utilized as an advanced bio-tribometer.
Keywords: ortopedie; tření; mechanické jevy; testování materiálů; povrchové vlastnosti; Friction; Wear debris; Prostheses and Implants; kyčelní kloub; Materials Testing; Micro dimple; Surface Properties; Hip joint prosthesis; Diamond like carbon; Orthopedics; Mechanical Phenomena; protézy a implantáty; Hip Joint; Friction coefficient; Diamond; diamant